PENGARUH SIKAP DAN NORMA SUBYEKTIF TERHADAP MINAT MAHASISWI UNIVERSITAS TADULAKO MEMBELI LIPSTIK MEREK LA TULIPE - AMALIAH, DITA (Fakultas Ekonomi Universitas Tadulako, 2017)
The purpose of this study is to learn and increase student?s interest in Tadulako University on purchasing brand lipstick La Tulipe. The variables of this research are attitude (X1) and subjective norm (X2), and the dependent variable is interest (Y). The research method used in this study is descriptive causal method with 61 sample and purposive sampling technique and method of analysis, Multiple Linear Regression with the help of computer program SPSS for windows, Release 16.0. The results showed that : 1). Subjective Attitudes and Norms Simultaneously Significantly Affects Student Interest The University of Tadulako buys La Tulipe brand lipstick; 2). Attitudes partially significant effect on Student Interest TadulakoUniversity bought brand lipstick La Tulipe; 3). Subjective Norms partially significant effect on Student Interest University Tadulako buy brand lipstick La Tulipe.